Neural Basis of Action Observation and Understanding From First- and Third-Person Perspectives: An fMRI Study - Ge, Sheng; Liu, Hui; Lin, Pan; Gao, Junfeng; Xiao, Chaoyong; Li, Zonghong (Frontiers in Behavioral Neuroscience, 2018)
Understanding the intentions of others while observing their actions is a fundamental aspect of social behavior. However, the differences in neural and functional mechanisms between observing actions from the first-person perspective (1PP) and third-person perspective (3PP) are poorly understood. The present study had two aims: (1) to delineate the neural basis of action observation and understanding from the 1PP and 3PP; and (2) to identify whether there are different activation patterns during action observation and understanding from 1PP and 3PP. We used a blocked functional magnetic resonance imaging (fMRI) experimental design. Twenty-six right-handed participants observed interactions between the right hand and a cup from 1PP and 3PP. The results indicated that both 1PP and 3PP were associated with similar patterns of activation in key areas of the mirror neuron system underlying action observation and understanding. Importantly, besides of the core network of MNS, we also found that parts of the basal ganglia and limbic system were involved in action observation in both the 1PP and 3PP tasks, including the putamen, insula and hippocampus, providing a more complete understanding of the neural basis for action observation and understanding. Moreover, compared with the 3PP, the 1PP task caused more extensive and stronger activation. In contrast, the opposite comparison revealed that no regions exhibited significantly more activation in the 3PP compared with the 1PP condition. The current results have important implications for understanding the role of the core network underlying the mirror neuron system, as well as parts of the basal ganglia and limbic system, during action observation and understanding.